A Metaphorical Approach to Developing Behavior Within the Context of the Covid-19 Pandemic - Ceren Yegen; Arthur Berger (Türkiye İletişim Araştırmaları Dergisi)
Although the COVID-19 Pandemic is a global health crisis, it is an epidemic that re-regulates many areasof life and profession. This study focused on designs made by independent designers to protect and helpprotect people from disease. So, the relevant tendency is important in raising awareness and improvingthe desired behavior during the current COVID-19 pandemic. For this reason, the iconic designs of anindependent designer in Turkey were examined to raise awareness at the point of the pandemic. Thus, itis aimed to understand the role of visuals in raising awareness and creating behavior. In the analysis, thesemiotic analysis method was used. According to the analysis, it is seen that the examined visuals are quiteremarkable often calling for protection from the new Coronavirus through euphemism and often usingmetaphors. On the other hand, it may be thought that the visuals examined may not convince everyoneto be careful and avoid exposure to the virus. In the study, a social network analysis was also conducted tounderstand the appearance and interaction status of the pandemic in social networks, and the networks‘#evdekal’ (stay at home) and ‘#hayatevesigar’ (life fits into the home) on Twitter were examined. The resultsof the social network analysis show that the course of the pandemic did not arouse public reaction (inthe scope of the analysis period). However, the fact that close connections cannot be established betweendifferent networks and the presence of the government party and the Minister of Health in the networks isalso important in terms of public opinion and interaction.